Predicting the Performance of Small Aquaculture Businesses in Kelantan through Marketing and Logistics Practices - Rosli, M. Mohd; Fitriah, A.W. Nurul; yaacob, Abdul aziz; Mustapha, N.Z. Aniesha, Nora’Ani; Aziz, Zuraimi Abdul; Ibrahim, Wan Mohd Yusuff Wan; Radzi, Mohd Shahril Nizam Md.; Rosdi, Radzi, Siti Nabila (International Journal of Supply Chain Management, 2018)
Business performance at production level would influence the overall performance of the aquaculture industry. Many factors can be associated with business performance. It has been argued that a good marketing and logistics practice would lead to a positive business performance. However, it may not be always true for all types of industry, setting and condition. This study examined the effects of marketing and logistics on small business performance in the Kelantanese aquaculture industry. Using a self-administered questionnaire, data were collected from 216 respondents in small aquaculture in Kelantan. The Partial Least Squares Analysis (PLS) was employed to examine the relationship between the marketing, logistics and business performance variables. It was found that only one of the four marketing variables, i.e. place, explained the variation in business performance. But, it had a wrong sign that was negative, instead of a positive sign. On the contrary, two out of three logistics variables (transportation and order processing) influenced the changes in business performance. In the condition of excess demand, marketing did not work, whereas logistics was more important. Thus, a good practice in logistics is more important than that of marketing for small aquaculture businesses.